Retrospective Analysis of Prosthetic Complications of Implant-Supported Fixed Partial Dentures After an Observation Period of 5 to 10 Years - ÖZKAN, YASEMİN; ÖZKAN, YAŞAR (QUINTESSENCE PUBLISHING CO INC, 2013)
Purpose: The purpose of this study was to evaluate the incidence of the most common technical problems with implant-supported fixed partial dentures (FPDs) and to assess the survival and success rates (event-free survival) after 5 to 10 years of function. Materials and Methods: All of the implants evaluated in this study were from a single manufacturer (Institut Straumann). Follow-up examinations were scheduled 1 week after suprastructure placement, 6 months later, and annually thereafter. Prosthesis-based data on survival/failure rates and technical complications were analyzed. Results: In 95 partially edentulous patients, 231 Straumann implants were placed and restored with 177 implant-supported prostheses (125 single crowns, 18 splinted crowns on two adjacent implants, and 34 three-unit FPDs). One hundred thirty-one solid abutments and 100 synOcta abutments were inserted. The survival rate of prostheses supported by implants was 97.7%. The prosthetic success rate (event-free survival) was 96.05%. After an observation period of 5 years, the cumulative incidence of screw loosening was 0%. Fracture of the veneering porcelain occurred in 3.95% of all restorations. Fractures of the superstructure framework were not observed. The overall incidence of complications after 5 years was highest for splinted crowns, which showed the lowest success rate (94.4%), followed by three-unit FPDs (96%) and single crowns (98.4%). Conclusions: Single-unit restorations or short-span FPDs supported by both synOcta and solid abutments on Straumann implants showed low rates of technical complications, the most common being fracture of the veneering porcelain.
Keywords: abutment; fixed partial dentures; implant; prosthetic outcome; PARTIAL EDENTULISM; DENTAL IMPLANTS; TECHNICAL COMPLICATIONS; POSTERIOR REGION; SINGLE CROWNS; SURVIVAL; RESTORATIONS; FAILURES; RATES